Participação dos receptores gabaérgicos, serotoninérgicos e adrenérgicos do núcleo do trato solitário na ingestão de água e sódio induzida por diferentes tipos de desidratação - Tomeo, Rodrigo Anderson (2016)
The nucleus of the solitary tract (NTS), the primary site of peripheral osmoreceptor and cardiovascular afferences, is suggested to receive important inhibitory signals involved in the control of water and sodium intake. However, it is not known which neurotransmitters are involved in the transmission of this information. Central gabaergic, serotonergic and adrenergic mechanisms are involved in the control of sodium and water intake and immunohistochemical studies have shown that these receptors are present in the NTS. Therefore, in the present study, we investigated the effects of muscimol (a GABAA receptor agonist), DOI (a serotonergic 5-HT2A/2C receptor agonist), methysergide (a serotonergic 5-HT1/2 receptor antagonist) and moxonidine (α2 adrenergic/imidazoline receptor agonist) injected into the NTS on water and 0.3 M NaCl intake induced by intragastric load of 2 M NaCl (a cellular dehydration protocol), by intracerebroventricular (icv) angiotensin II (ANG II) or by sodium depletion (furosemide + 24 h diet deficient in sodium, a extracellular dehydration protocol). Holtzman rats (290-310 g, n=3-20) had stainless steel cannulas implanted bilaterally into the NTS and into the lateral ventricle (LV). Bilateral injection of muscimol (0.25 and 0.5 nmol/100 nl), and DOI (2.5 μg/100 nl) reduced water intake induced by intragastric load of 2 M NaCl (2 ml/rat) and water intake induced by icv ANG II (50 ng/100nl) without changing 0.3 M NaCl intake. Bilateral injection of DOI reduced water intake induced by icv ANG II. However, DOI produced no changes in the 0.3 M NaCl and water intake induced by sodium depletion. Injections of methysergide (2 μg/100 nl) produced no changes in the water and 0.3 M NaCl intake induced by intragastric load of 2 M NaCl, icv ANG II or sodium depletion. The pre-treatment with methysergide blocked the effect of DOI on water intake induced by intragastric load of 2 M NaCl. Besides that, bilateral injections of moxonidine (0.5 and 5 nmol/100 nl) produced no changes on water intake induced by intragastric load of 2 M NaCl. The results suggest that gabaergic, serotonergic, but not adrenergic, receptors in the NTS are part of a mechanism involved in the inhibitory control of water intake induced by cellular dehydration. Our results also suggest that serotonergic receptors into the NTS participate in the control of water intake induced by icv injection of ANG II.